Proceedings of the 8th International Conference on foundations of computer-aided process design - International Conference on Foundations of Computer-Aided Process Design (8th); Towler, Gavin P., editor; Eden, Mario R.; Siirola, John D., editor (Oxford : Elsevier, 2014)
Includes bibliographical references and index